2016
DOI: 10.1007/s10570-016-0908-z
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of structural changes in cellulosic substrates during enzymatic hydrolysis using multimodal nonlinear microscopy

Abstract: Enzymatic hydrolysis of cellulose provides a renewable source of monosaccharides for production of variety of biochemicals and biopolymers. Unfortunately, the enzymatic hydrolysis of cellulose is often incomplete, and the reasons are not fully understood. We have monitored enzymatic hydrolysis in terms of molecular density, ordering and autofluorescence of cellulose structures in real time using simultaneous CARS, SHG and MPEF microscopy with the aim of contributing to the understanding and optimization of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…In sugar cane bagasse samples, it was shown that after chemical bleaching, which removes lignin, fibril packages of bagasse sample partially lost their longitudinal orientation . In situ enzymatic hydrolysis imaging of pretreated softwood revealed that SHG signal decreased at increasing hydrolysis, indicating the conversion of cellulose to monosugars as it was also shown here. Additionally, the autofluorescence signal was shown to decrease after hydrolysis; however, the origin of the signal was not attributed to a specific source.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…In sugar cane bagasse samples, it was shown that after chemical bleaching, which removes lignin, fibril packages of bagasse sample partially lost their longitudinal orientation . In situ enzymatic hydrolysis imaging of pretreated softwood revealed that SHG signal decreased at increasing hydrolysis, indicating the conversion of cellulose to monosugars as it was also shown here. Additionally, the autofluorescence signal was shown to decrease after hydrolysis; however, the origin of the signal was not attributed to a specific source.…”
Section: Resultssupporting
confidence: 83%
“…Finally, TPM when combined with fluorescence lifetime imaging microscopy (FLIM) can provide chemical information of the sample. TPM has been used for imaging lignocellulosic samples, such as sugar cane bagasse samples, soft wood, and poplar and wheat straw, in order to investigate the morphological and chemical changes induced by different pretreatments, and enzymatic hydrolysis. Hereto, the autofluorescence properties of the plant cell wall polymers were first investigated and afterward used to interpret the autofluorescence signal of pCS samples.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the Amati SC1 sample, despite being older and mildly treated with chemicals, still shows strong SHG signals. SHG is a non‐linear optical phenomenon associated with non‐centrosymmetry, arising from cellulose microfibrils with helical twists [37] . Diminished SHG suggests conformational changes and rearrangements of cellulose chains.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a nearly-identical image is obtained via contrast for benzonitrile in the "silent region" at 2240 cm 1 (not shown), however, we chose 3074 cm 1 and 2934 cm 1 as the two CARS contrasts to highlight the spectral sensitivity of our SF-CARS system. Stimulated vibrational imaging of cellulose, both at the fingerprint [17,30] and CH-OH frequency ranges [31][32][33], has been previously demonstrated. In our sample, the CARS signal from cellulose at 1100 cm 1 is detected, but the signal is largely swamped by the large NRB from the solvents that soak the fibre.…”
Section: Resultsmentioning
confidence: 99%